APPLICATION OF BUILDING INFORMATION MODELLING (BIM) IN A RESIDENTIAL PROJECT IN INDIA: BENEFIT-COST ANALYSIS - Thakkar, Harshil; Pandya, Bhishma; Rabadiya, Mihir; Prajapati, Rakesh; Thakkar, Dhwani (International Journal of Engineering Technologies and Management Research, 2021)
Building information (BIM) is becoming a better-known collaboration process in our construction industry. BIM is a systematic process that amalgamates all the other geometric computer-generated models, or data that creates simulations that can be used for the project manager, owners, facility manager or other parties to look after the project and deliver the project more efficiently. The implementation of BIM in India is still at a nascent stage due to a lack of knowledge of the advantages of BIM. Moreover, there have been only a few case studies conducted in India about BIM; therefore, the principal agenda of this study is to enlighten the readers about the benefits accrued if BIM is applied, in the residential project, before the construction. Hence, the authors had taken a residential project located in Gujarat, India, for a case study. The 3D and 4D models of the project were generated; 8 errors were identified that could have been detected before construction if BIM had been applied. The cost needed to make a BIM model was ₹ 171,050. Whereas, the amount that could have been saved if BIM was implemented beforehand was discovered as ₹ 246,773. Consequently, the benefits to cost ratio for two weeks in delay was determined as 1.44. It can be as the benefit of BIM for construction.